Impact of volatile allyl isothiocyanate on fresh produce. (June 2018) - Kramer, B.; Wunderlich, J.; Muranyi, P.
Highlights: Gaseous allyl isothiocyanate was evaluated as natural preservative for packaged fresh produce. Gaseous allyl isothiocyanate exhibits antimicrobial activity on sprouts and iceberg salad. Even low amounts of allyl isothiocyanate negatively affect the quality of sprouts and iceberg salad. Abstract: The applicability of allyl isothiocyanate (AITC) for the preservation of mung bean sprouts as well as fresh-cut iceberg lettuce was investigated. For this purpose, produce samples were stored in high gas barrier plastic bags containing a filter paper soaked with AITC (10 μl). Microbial loads as well as color changes and respiration of both products were monitored over 9 days of storage at 5 °C. The results showed that AITC (0.81–1.41 μg/ml) exhibits strong antimicrobial properties via the gas phase against the native microflora of iceberg lettuce and mung bean sprouts. However, the quality of both tested products was significantly affected, which limits the applicability of AITC for such sensitive produce commodities. The respiration activity of mung bean sprouts and fresh-cut salad was decreased by AITC while discolorations as well as changes to the texture were evident even at low concentrations (0.11–0.16 μg/ml), which did not provide antimicrobial effects.